Navigating the economic landscape: A comprehensive analysis of government spending, economic growth, and poverty reduction nexus in Tanzania - Kitole, Felician A.; Msoma, Liberati J.; Sesabo, Jennifer K. (Applied Economics Letters, 2024)
Paper presented to the Applied Economics Letters of 2024